Carbapenem-Resistant Enterobacteriaceae Acquired Before Liver Transplantation: Impact on Recipient Outcomes. Issue 4 (April 2017) - Freire, Maristela Pinheiro; Oshiro, Isabel C. V. S.; Pierrotti, Ligia C.; Bonazzi, Patricia R.; de Oliveira, Larissa M.; Song, Alice T. W.; Camargo, Carlos H.; van der Heijden, Inneke M.; Rossi, Flavia; Costa, Silvia F.; D'Albuquerque, Luiz A. C.; Abdala, Edson
Abstract : Background: Carbapenem-resistant Enterobacteriaceae (CRE) is an emergent microorganism of infections after liver transplant (LT). The aim of this study was to analyze the risk factors for CRE acquisition and infection after LT. Methods: This was a prospective cohort study involving patients who underwent LT in the 2010 to 2014 period. Surveillance cultures for CRE were collected immediately before LT and weekly thereafter until hospital discharge. Results: We analyzed 386 patients undergoing a total of 407 LTs. Before LT, 68 (17.6%) patients tested positive for CRE, 11 (16.2%) of those patients having CRE infection, whereas 119 (30.8%) patients acquired CRE after LT. Post-LT CRE infection was identified in 59 (15.7%) patients: Klebsiella pneumoniae was isolated in 83.2%; surgical site infection was the most common type of infection (46.7%). Multivariate analysis showed that post-LT dialysis was the only risk factor for post-LT CRE acquisition. Eighty-two percent of patients who underwent 3 or more post-LT dialysis sessions and acquired CRE before LT evolved with post-LT CRE infection. Other risk factors for CRE infection were acquisition of CRE post-LT, Model for End-Stage Liver Disease score greater than 32, combined transplantation, and reoperation. Patients who acquired CRE before LT had a high risk of developing CRE infection ( P < 0.001). Conclusions: Measures for minimizing that risk, including altering the antibiotic prophylaxis, should be investigated and implemented. Abstract : The authors of this prospective study establish risk factors for carbapenem-resistant Enterobacteriaceae, an emergent microorganism of infections after liver transplantation, highlighting that colonization before transplantation is one of the main risk factors that could potentially be targetted with adequate antibiotic prophylaxis. Supplemental digital content is available in the text.